A Study on Risk Factors Associated with Reflux Esophagitis in Patients Undergoing Esophageal Cancer Surgery. (27th March 2022) - Wang, Ping; Liu, Chunzhi; Wei, Lianmin; Wei, Wenchao; Liu, Zhao; Wu, Fengting; Qu, Rui
Abstract : Objective . To investigate the risk factors associated with reflux esophagitis in patients undergoing esophageal cancer surgery and to provide reference for the prevention and treatment of reflux esophagitis. Methods . In the manner retrospective study, the data of 300 patients with esophageal cancer who received the surgical treatment in our hospital (January 2018–December 2020) were retrospectively reviewed. The 300 patients were divided into the occurrence group ( n = 45) and nonoccurrence group ( n = 255) depending on whether they had reflux esophagitis after surgery. The social demographic data and clinical data of the patients in the two groups were collected. These data were classified into the personal factors and surgical factors. The single-factor analysis method was adopted to analyze the effects of the personal and surgical factors on reflux esophagitis. The factors with statistically significant differences in the single-factor analysis were analyzed by logistic regression to verify the factors were the risk factors associated with reflux esophagitis in patients undergoing esophageal cancer surgery. Results . The differences in the bodyweight, body mass index (BMI), length of the resected esophagus, surgical approach, intraoperative blood loss, gastrointestinal decompression volume, and surgery time between the two groups were of statistical significance (P < 0.05 ). After being tested by the logistics multivariate analysis, length of the resected esophagus, whole stomach reconstruction, intraoperative blood loss, and surgery time were identified as the risk factors associated with reflux esophagitis in patients undergoing esophageal cancer surgery. Conclusion . The length of the resected esophagus, whole stomach reconstruction, intraoperative blood loss, and surgery time were the risk factors associated with reflux esophagitis in patients undergoing esophageal cancer surgery. It is necessary to choose the appropriate surgical approach according to the patients' conditions in practice and to strengthen the prevention and treatment of reflux esophagitis.